Beyond Recording the Clinical Discussion: A Qualitative Study into Patient-Led Recordings in Hospital - Laura Ryan MS; Kelly A Weir PhD; Jessica Maskell PhD; Lily Bevan BS; Robyne Le Brocque PhD (Journal of Patient Experience, 2023)
Patient-led recording occurs when a patient records a clinical encounter with their smart device. Understanding patient-led recording is important in ensuring a safe and patient-centered response to this behavior. This exploratory study provides insight into the patient perspective of patient-led recordings. We conducted 20 semistructured interviews with hospital and health service patients. The interview data was analyzed using thematic analysis. We identified three themes relating to patient-led recordings, including patient engagement, psychosocial, and health service. Findings suggest that health services move beyond querying the permissibility of recording and consider how to maximize the benefits of recording while reducing the risk of harm. Patients and clinicians need to be made aware of the potential broader psychosocial benefits of recording a clinical encounter during hospital admission. These results point to an urgent need for health services to develop policies and resources that support clinicians to work within a culture of recording.